Model study evaluating environmental benefits uprova-tion cns/atm air traffic control technology - Бабак, В.П.; Бабейчук, Д.Г.; Запорожець, О.І. (Proceedings of National Aviation University (archive), 2012)
Previous results of different researches show that in 2015 it follows to expect the additional improvements in fuel consumption and decrease of CO2 emission on 5% by implementation of the CNS/ATM systems. Application of the CNS/ATM systems will benefit in three directions: improvement of carrying airport capacity, accordingly the reduction of number of delays in the loaded airports; shortening of flights’ duration due to the use of more direct routes; and reduction of the vertical echeloning (RVSM). A parametric model for the detailed research of influencing of height and speed of the aircraft flights on engine emission and fuel consumption was developed, it allows to evaluate an ecological efficiency of the implementation of CNS/ATM technologies.